2014
DOI: 10.4136/ambi-agua.1220
|View full text |Cite
|
Sign up to set email alerts
|

Viabilidade do uso de água residuária tratada na irrigação da cultura do rabanete (Raphanus sativus L.)

Abstract: The use of treated wastewater for irrigation may become an alternative for regions facing water scarcity. This study aimed to evaluate the effects of wastewater reuse in the cultivation 110 Iasmine Louise de Almeida Dantas et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 7 publications
2
12
0
11
Order By: Relevance
“…Soil fertility is evaluated by measuring chemical properties such as pH, organic matter, phosphorus, potassium, calcium, magnesium, aluminum + hydrogen, cation exchange capacity, base saturation and others (Reichardt and Timm, 2004), so it is important to note that the presence of these nutrients in treated wastewater is a problem only when their concentrations are too high once the treated wastewater can be used as a fertilizer supply (Baumgartner et al, 2007;Dantas et al, 2014;Cuba et al, 2015;Gabrielli et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Soil fertility is evaluated by measuring chemical properties such as pH, organic matter, phosphorus, potassium, calcium, magnesium, aluminum + hydrogen, cation exchange capacity, base saturation and others (Reichardt and Timm, 2004), so it is important to note that the presence of these nutrients in treated wastewater is a problem only when their concentrations are too high once the treated wastewater can be used as a fertilizer supply (Baumgartner et al, 2007;Dantas et al, 2014;Cuba et al, 2015;Gabrielli et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, there are studies of WWTP irrigation agriculture in different cultures. Dantas et al (2014), using WWTP of the city of São Cristóvão-SE to irrigate radishes, found that the resulting radishes were within the standards established by law. Deon et al (2010) and Freitas et al (2013) showed gains in productivity of cane sugar with drip irrigation of effluent.…”
Section: Introductionmentioning
confidence: 83%
“…The physicochemical characteristics of the RW suggest that it is suitable for crop irrigation, namely for the irrigation of fruit trees and vinery (Asano et al, 2007;Dantas et al, 2014). It has moderate organic content, high nutrient content (which is useful for crop production), low nitrate concentrations (it does not present a risk for groundwater contamination), low heavy metal concentrations, low EC (only values above 0.7 dS m -1 may be considered a risk for soil salinity) and is not phytotoxic for those crops (the concentration of Al, B, Cl and Na are below the recommended values for crop irrigation set up in USEPA (2012), Asano et al (2007).…”
Section: Site Location For Reclaimed Water Reusementioning
confidence: 99%
“…Sendo assim, a sua disponibilidade está diretamente relacionada com o aumento da produtividade nas áreas agrícolas (Falloon e Betts, 2010). Sabe-se que, a nível mundial, a irrigação é a maior consumidora de água derivada das fontes como rios, lagos e aquíferos subterrâneos (Dantas et al, 2014). Entretanto, uma das principais dificuldades do setor agrícola tem sido a disponibilidade desse recurso (Falloon e Betts, 2010).…”
Section: Introductionunclassified